2022
DOI: 10.1007/s00497-022-00451-6
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral self-compatibility facilitates the establishment of allopolyploids in Brassicaceae

Abstract: Self-incompatibility systems based on self-recognition evolved in hermaphroditic plants to maintain genetic variation of offspring and mitigate inbreeding depression. Despite these benefits in diploid plants, for polyploids who often face a scarcity of mating partners, self-incompatibility can thwart reproduction. In contrast, self-compatibility provides an immediate advantage: a route to reproductive viability. Thus, diploid selfing lineages may facilitate the formation of new allopolyploid species. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 181 publications
2
13
0
2
Order By: Relevance
“…In the specific case of allopolyploidy in Brassicaceae, our results formally establish that the mating system immediately upon hybridization depends on the relative dominance of the non-functional allele inherited from the selfer C. orientalis as compared to that of the functional S-allele(s) inherited from the outcrosser C. grandiflora, in line with the model proposed by Novikova et al (2022). This observation raises at least three intriguing questions.…”
Section: Brassicaceaesupporting
confidence: 85%
See 2 more Smart Citations
“…In the specific case of allopolyploidy in Brassicaceae, our results formally establish that the mating system immediately upon hybridization depends on the relative dominance of the non-functional allele inherited from the selfer C. orientalis as compared to that of the functional S-allele(s) inherited from the outcrosser C. grandiflora, in line with the model proposed by Novikova et al (2022). This observation raises at least three intriguing questions.…”
Section: Brassicaceaesupporting
confidence: 85%
“…Some factors affecting the fixation probability of SC mutations have been studied by Tsuchimatsu & Shimizu (2013), but to the best of our knowledge, the effect of dominance on the fixation probability of SC mutations in a sporophytic SI system remains to be investigated formally. A third interesting question is why most known examples of recent allotetraploids in Brassicaceae involve hybridization between a selfer and an outcrosser (Novikova et al 2022). A more general survey of recent allopolyploids would be needed to determine the generality of this pattern, but one tempting hypothesis is that, given an appropriate combination of S-haplotypes, this kind of crosses might instantaneously generate SC allotetraploid individuals avoiding minority cytotype exclusion (Novikova et al 2022).…”
Section: Brassicaceaementioning
confidence: 99%
See 1 more Smart Citation
“…Husband et al . [21] showed that autopolyploid species generally self-fertilize less than diploid ones, while allopolyploids showed the opposite pattern [21,63]. Since our dataset is mainly composed of autopolyploid species (table 1), our finding seems to be counterintuitive.…”
Section: Discussionmentioning
confidence: 80%
“…Husband et al . [21] showed that autopolyploid species generally self-fertilize less than diploid ones, while allopolyploids showed the opposite pattern [21,37]. Since our dataset is mainly composed of autopolyploid species (Table 1), our finding seems to be counterintuitive.…”
Section: Discussionmentioning
confidence: 82%